Unicompartmental Knee Arthroplasty for Knee Osteoarthritis With the Pellegrini–Stieda Lesion: A Case Report - Wang, Qiuyuan; Guo, Wanshou; Shi, Zhencai; Wang, Weiguo; Zhang, Qidong (Frontiers in Surgery, 2022)
Pellegrini-Stieda lesion was described as ossification on the origin of medial collateral ligament (MCL). We present a case of end-stage knee osteoarthritis with Pellegrini-Stieda lesion treated by unicompartmental knee arthroplasty (UKA). During the postoperative follow-up, amazing change occurred that the ossification lesion disappeared gradually and did not relapse. It was supposed that the disappeared ossification was due to UKA changed the abnormal biomechanics of the varus osteoarthritic knee.